Photographic Evidence of Management of Allergic Contact Dermatitis with Graphites 30C - A Case Report (Advancements in Homeopathic Research, 2022)
One of the major occupational risks for people  working in the construction or cement industries is  allergic contact dermatitis, which frequently affects  the workers' quality of life and results in significant  financial loss. The hands of cement workers come into  touch with cement on a frequent basis, making them  susceptible to developing hand contact dermatitis  again and making a full recovery exceedingly  challenging. The contact dermatitis in homoeopathy  has been the subject of numerous prior researches.  This case study demonstrated the effectiveness of  the homoeopathic drug Graphites 30C on allergic  contact dermatitis, with slow improvement at first  and full recovery at the end.
Keywords: Allergic contact dermatitis; cement worker; occupational dermatitis; Graphites; Homoeopathy